Determinants of Accountability for Financial Management of Non-Profit Organizations in Indonesia with the Internal Control and Supervision Environment as Moderation Variables - Amirah, Amirah; Totanan, Chalarce; Jurana, Jurana (Ridwan Institute, 2024)
This study aims to examine the determinants of financial management accountability in non-profit organizations. Utilizing a quantitative methodology employing Partial Least Squares (PLS) analysis, the study assessed 14 hypotheses, relying on coefficient values and significance levels for hypothesis validation. While the choice of analysis model and rationale behind its selection were not explicitly elucidated, the study ensured rigor through pilot testing of the questionnaire to establish validity and reliability. From 140 distributed questionnaires, 87 were returned, and 79 met the inclusion criteria for analysis. The findings suggest a significant positive influence of transparency, fund type, financial statement presentation, and accessibility on financial management accountability. Additionally, internal control factors such as transparency, fund types, financial statement presentation, accessibility, and internal supervision underscore the importance of these elements in bolstering accountability. However, it is noteworthy that the direct impact of the control environment on financial management accountability was not observed within the study's context. While the identification and operationalization of the studied variables were not extensively detailed, it is acknowledged that the relatively small sample size and the focus solely on non-profit organizations in Indonesia may constrain the generalizability of the findings. Nonetheless, this research provides valuable insights into the factors influencing accountability practices in NGO financial management, potentially benefiting stakeholders and contributing to the existing literature on financial management, particularly within the realm of non-profit entities.